Training load and time-in-range affect sleep time of professional cyclists with type 1 diabetes - Scott, S. N.; Fontana, F. Y.; Martinez-Gonzalez, B.; Hayes, C. A.; Lagrou, P. H.; Marcora, S.; Zueger, T.; Stettler, C. (Diabetes, 2020)
Background and Aims: People with type 1 diabetes (T1D) experience higher rates of sleep disturbances than those without diabetes, and this can have negative implications for glycemic control. Sleep is critical for optimal athletic performance and recovery so it is important to have an understanding of factors that can influence sleep in athletes with T1D. This study investigated whether there is a relationship between i) daily training load and ii) time in glycemic ranges on sleep time of professional cyclists with T1D.